2015
DOI: 10.18579/jpcrkc/2015/14/1/78376
|View full text |Cite
|
Sign up to set email alerts
|

Review on Niosomes - a Novel Approach for Drug Targeting

Abstract: Purpose: This is a general review on niosome as drug carrier, which improves the bioavailability of drugs, increases penetration through skin, releases drug in a controlled or sustained manner, and used for targeting of drugs to specic sites in the body. Approach: Niosomal drug delivery system can be considered as an emerging novel drug delivery system, which consists of microscopic non-ionic vesicles composed of non-ionic surfactants. These are biodegradable, relatively nontoxic, more stable and inexpensive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Using the Malvern Zetasizer Nano, it was found that the average size of the majority of the green tea extract niosomes vesicles was 1109 nm or 1.109 µm and the particle distribution showed a PdI of 0.856 (Table 3). These niosomes can be classified as large unilamellar vesicles because the size of the vesicles was more than 0.10 µm (Sudheer & Kaushik, 2015). It was also found that the particle size distribution of green tea extract niosomes was very broad, because they had a PdI value >0.7 (Nidhin et al, 2008).…”
Section: Niosomes Characterisationmentioning
confidence: 97%
“…Using the Malvern Zetasizer Nano, it was found that the average size of the majority of the green tea extract niosomes vesicles was 1109 nm or 1.109 µm and the particle distribution showed a PdI of 0.856 (Table 3). These niosomes can be classified as large unilamellar vesicles because the size of the vesicles was more than 0.10 µm (Sudheer & Kaushik, 2015). It was also found that the particle size distribution of green tea extract niosomes was very broad, because they had a PdI value >0.7 (Nidhin et al, 2008).…”
Section: Niosomes Characterisationmentioning
confidence: 97%
“…Specialized niosomes are called proniosomes; these are nonionic based surfactant vesicles, which are hydrated immediately before use to yield aqueous niosome dispersions. To enhance drug delivery in addition to conventional niosomes, proniosomes are also being used [ 41 , 42 ].…”
Section: Novel Nanocarriers For Cosmeceuticalsmentioning
confidence: 99%
“…The samples are taken out at suitable time intervals, replaced with fresh media and analyzed for drug content. 28…”
Section: Franz Diffusion Cellmentioning
confidence: 99%